A new Paxillus MacLeay, 1819 (Coleoptera: Passalidae: Passalinae) from Brazilian Amazon - Ribeiro, Jefson Morais; Fonseca, Claudio Ruy Vasconcelos Da (Instituto de Ecología, A.C., 2019)
Paxillus MacLeay, 1819 is a genus widely distributed throughout the Americas and currently holds sixteen species. Seven species are known in the Amazon. Herein Paxillus elatus n. sp. is described and illustrated based on eight males and four females collected in the Brazilian Amazonian states Acre, Amazonas and Rondônia.